The Role of Human Capital in Technological Entrepreneurship - Wright, Mike; Hmieleski, Keith M.; Siegel, Donald S.; Ensley, Michael D. (Entrepreneurship Theory and Practice, 2007)
This special issue addresses the role that the human capital characteristics of individuals and teams play in the complex process of technological entrepreneurship. In this article, we position the special issue on human capital and technology–based entrepreneurship within the literatures concerning academic entrepreneurship, technology transfer and innovation, and corporate spin–offs. We summarize the articles in the special issue and also outline a research agenda at the firm, entrepreneurial team, and individual entrepreneur levels. Finally, we discuss managerial and policy implications.